Evolución de las expectativas de inflación en México - Santiago García-Verdú (Banco de México, 2012)
– This paper presents an analysis of the expected inflation distribution based on the surveys made to economic analysts in the private sector, by Banco de México. Conceptually, the analysis can be divided into three aspects: level, dispersion, and skewness, of expected inflation. It is anticipated that the behavior of these aspects will be consistent with the process of inflation convergence to its target, in the sense that the expected inflation level and dispersion, and the probability of observing a sizable realization of inflation have been diminishing, as the cited process has taken place. Additionally, first, a model is presented in which agents face a cost when they update their in ation expectation. This model explains some of the facts seen in inflation expectation dispersion. In the model, the decrease in the dispersion is consistent with an increase in the frequency with which the agents update their inflation expectation, as observed in the data. Second, under an event-study framework the respond of upside risks of inflation expectations to the approval of the Income Law is analyzed. The results suggest that once the cited law is approved, on average there is a decrease in such risks.
Keywords: E31; D84; 330; Inflation; Expectations; Expected Inflation; Inflationserwartung; Mexiko